Behavior of Plastic Tubular Specimens Filled with Brick-Aggregates Concrete Under Compressive Loads - Sadiq Al-Aasam, Haider; Yousif Hassan, Ruaa; Jawad Aziz, Riyadh (International Journal of Engineering and Technology, 2018)
This study represents results of an experimental test to investigate the effect on the compression strength of gravel and recycled brick aggregates concrete specimens confined using plastic tubes. Plastic tubes used to confine concrete which is produced using river gravel or broken brick as a replacement for river gravel. A compressive load was applied to the specimens gradually up to failure.The results have indicated that as concrete compressive strength increased from (21.0 to 27.5)MPa, an increase in peak load of (3-46)% was achieved. Moreover, the brick aggregates concrete specimens have lower peak load as compared to gravel concrete and the peak load of confined specimens increased (3-6) times as compared to unconfined. Also, when the ratio of (height/diameter) of the concrete specimen increases from (2-4) the peak load decreased by about (2-12)%.The use of brick aggregates as a replacement to river aggregates results in significant decrease in weight and cost of concrete members. As well, the use of plastic tubes as a concrete form is superior to other construction materials such as wood or steel forms, since plastic tubes reduce the cost of forms and time of construction, and it protects concrete used for underground construction.Â Â Â